Ipsilateral Recurrence of Nonarteritic Anterior Ischemic Optic Neuropathy: A Case Report - Brigham, Daniel (Canadian Journal of Optometry, 2020)
Nonarteritic anterior ischemic optic neuropathy (NA-AION) is a multifactorial disease that represents the most common type of ischemic optic neuropathy. NA-AION develops in one eye and can occur in the fellow eye at a later date.1The recurrence of ipsilateral NA-AION is rare and a multitude of theories have arisen to explain this infrequent recurrence.2 This case report describes an incident of unilateral recurrence of NA-AION, explores the proposed etiologies, and will emphasize visual symptoms following its resolution. Key words. optic nerve edema Ÿ recurrent Ÿ nonarteritic ischemic optic neuropathy Ÿ contrast sensitivity Ÿ peripapillary retinal nerve fiber layer (pRNFL)